Performance of the CSR Program in the Small Medium Enterprise (SMEs) Financial Capacity Building - Purwanto Purwanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The Corporate Social Responsibility (CSR) program in developing the capacity of SMEs is not only related to training and credit assistance in the short term, but needs to be directed towards self-regulated of access to finance for SMEs, through collaboration with both financial and non-financial institutions. This study aims to analyze the performance of the CSR program in developing the financial capacity of SMEs, which is the relationship between financial literacy development, collaboration capacity and financial performance of SMEs. The research was conducted on 142 SMEs of CSR Program Partners of one of the state-owned enterprises in Indonesia. The research was conducted using qualitative data obtained through interviews with the owner-manager of UKM. Data analysis was performed using Structural Equation Modeling (SEM). The results of the study generally found that the development of SME financial literacy has an effect on the financial performance of SMEs either directly or through mediation of collaborative capacity. The indirect effect of developing SME financial literacy on SME financial performance through collaboration capacity is greater than the direct effect on business growth. The results of this study imply that the role of the government, private sector or donor agencies in empowering SMEs such as the SME financial capacity building program needs to be directed at developing literacy and collaboration skills, especially in the era of knowledge. Keywords: CSR program, financial literacy, financial access capacity, SME growth